2020
DOI: 10.15503/jecs20141.79.86
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of dual task (fine motor precision + cognitive charge) on proprioception

Abstract: The aim of the given preliminary study was to check whether any changes in fi ne motor behaviour exist in switching from single to double task (with cognition charge) in proprioceptive sensory graphomotor test conditions. Ten students (fi ve males and fi ve females), aged from 20 to 30 years old, took part in the experiment - precision of tracking of the models in both experimental test conditions: without and with cognitive task (counting numbers back). The variables for assessment were obtained with use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Changes in the precision of fine motor performance can occur due to changes in the environment and/or individual differences ( Tous Ral and Liutsko, 2014 ), stress and/or illness in patients with cancer ( Liutsko et al, 2016 ), Parkinson’s disease ( Gironell et al, 2012 ), multiple sclerosis ( Liutsko and Tous Ral, 2013 ), and developmental/maturation and aging processes ( Liutsko, 2014 ; Liutsko et al, 2014a , b ). Moreover, stress created by the simultaneous performance of tasks, such as the addition of a cognitive task like counting backwards from 100, to a fine motor performance task, also affected the fine motor precision of students on the Irritability dimension of DP-TC, causing an increase in Line Length performance 2 similar to what is observed due to aging processes ( Liutsko et al, 2014c ).…”
Section: Methodsmentioning
confidence: 86%
“…Changes in the precision of fine motor performance can occur due to changes in the environment and/or individual differences ( Tous Ral and Liutsko, 2014 ), stress and/or illness in patients with cancer ( Liutsko et al, 2016 ), Parkinson’s disease ( Gironell et al, 2012 ), multiple sclerosis ( Liutsko and Tous Ral, 2013 ), and developmental/maturation and aging processes ( Liutsko, 2014 ; Liutsko et al, 2014a , b ). Moreover, stress created by the simultaneous performance of tasks, such as the addition of a cognitive task like counting backwards from 100, to a fine motor performance task, also affected the fine motor precision of students on the Irritability dimension of DP-TC, causing an increase in Line Length performance 2 similar to what is observed due to aging processes ( Liutsko et al, 2014c ).…”
Section: Methodsmentioning
confidence: 86%
“…In a previous study, changes in proprioceptive accuracy of movements were found when switching from a single to a dual task, which corresponded to a shift towards the excitability pole in the balance of excitation-inhibition measurements [9]. Ingram and colleagues reported a significant decrease in motor task performance efficiency in a patient with proprioceptive problems, which decreased by 60% (compared to 10% in the control group) when the motor task was switched from single to double (with subjects counting backwards, which also creates a kind of situational stress) [10].…”
Section: Introductionmentioning
confidence: 79%
“…In the previous study, the change of task from single (just fine motor precision) to a dual one (combined with a cognitive charge ---counting back numbers), the changes were found in proprioceptive movement precision had occurred, such as increasing a line length that corresponded to the shift to the excitability pole in the Proprioceptive Diagnostic of Temperament and Character (DP-TC in Spanish original abbreviation) in a balance of Excitability-Inhibition dimension (Liutsko, Tous, & Segura, 2014). As indicate other studies, the proprioceptive fine motor precision depends on age, being worse while maturating (before 18 y.o.)…”
Section: Introductionmentioning
confidence: 98%